The Effect of CLS (Collecte Localisation Satellites) Application Use and Operator Readiness on Ship Monitoring Effectiveness at PT Sinarmas LDA Maritime - Putrie, Mayang Felishia; Indriyani, Kristin Anita; Prayogo, Darul; Anggrahini, Wahyu Prasetya; Sulistiyowati, Ely (Politeknik Ilmu Pelayaran Semarang, 2025)
The aim to be achieved in this research is to determine the significant influence of the use of the CLS (Collecte Localisation Satellites) application and operator readiness on the effectiveness of vessel monitoring at PT Sinarmas LDA Maritime. This research employs a quantitative method. Data collection techniques involve distributing questionnaires to respondents. The sampling technique applies Slovin’s formula, resulting in a final sample of 40 respondents who use the CLS application services. The data analysis method applied involves multiple linear regression, utilizing two independent factors and one dependent factor. The data is processed through multiple linear regression, incorporating classical assumption testing and hypothesis evaluation. As indicated According to the study results, the F-test indicates that the calculated F-value exceeds the F-table value (81.678 > 3.25), indicating that the use of the CLS application and operator readiness significantly influence the effectiveness of vessel monitoring. The findings conclude that in this study, the variables of CLS application usage and operator readiness (X1 and X2) have an impact on vessel monitoring effectiveness.